Scenario analysis of hydrofluorocarbons emission reduction in China's mobile air-conditioning sector (Advances in Climate Change Research, 2022)
With the Kigali Amendment (KA) coming into effect in China, the control of hydrofluorocarbons (HFCs) emissions has become more imperative. The mobile air-conditioning (MAC) sector is one of the important HFCs consumer sectors, and therefore studying its feasible mitigation paths and costs is of great significance to China's successful implementation of KA. This study used the bottom-up method with updated emission factors to re-evaluate the emission inventory of HFCs from the MAC sector in China from 2005 to 2020. The average annual growth rate of HFCs consumption in the MAC sector is 9.8%, and HFCs emissions have increased from 5.8 (5.3‒6.2) kt in 2005 to 22.2 (20.6‒23.8) kt in 2020, with an average annual growth rate of 8.8%. Using the Gompertz model combined with the Weibull function of vehicle survival rate, the ownership and new registrations of internal combustion engine vehicles (ICEVs) and electric vehicles (EVs) in China are predicted. The ownership of ICEVs and EVs is projected to be 310 million and 91 million in 2030, respectively and 2 million and 641 million in 2060, respectively. HFCs emissions in the MAC sector would reach 59.8 (55.3‒64.3) kt (80.0‒93.0 Mt CO2- eq) in 2060 if without any control measure. To implement the KA, the cumulative of 1.6 Gt CO2-eq emissions would be reduced. Under the other two accelerated mitigation scenarios, the MAC sector's HFCs will reach their emissions peak in 2028 and 2025 and achieve zero emissions in 2050 and 2046, respectively. Under the accelerated mitigation with recovery scenario, the cumulative emissions are only 15.0% of the business as usual (BAU) scenario. Using HFO-1234yf as the substitute, the unit abatement cost of the MAC sector is 27.3‒37.4 USD t−1 CO2-eq.